Factors affecting the employability skills of vocational students majoring mechanical engineering - Muhammad Noor Fitriyanto; Pardjono Pardjono (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This study aims to find out the significance of the direct effect of industrial work practices on work learning readiness, vocational competency, and employability skills, the direct effect of work learning readiness on employability skills, and the direct effect of vocational competency on employability skills. The significance of the effect founds was expected to enhance the knowledge and consideration for developing employability skills vocational high school (VHS) students especially at industrial work practice, work readiness, vocational competency at vocational high school. The research used a quantitative approach with ex-post facto type. The data were analyzed quantitatively to test the formulated hypothesis. The research was conducted at State and Private Vocational High School in Yogyakarta Special Region. The population of the study was grade XII students majoring mechanical engineering. The research samples were 444 students who were selected using proportionate stratified random sampling. The data collection techniques were questionnaires distribution and documentation. The content validity was established using expert judgment. The construct validity was established using analysis factor by Kaiser Meyer Olkin Measure of Sampling Adequacy (KMO MSA) with a value of 0.691. The reliability of the research was judged using Cronbach's alpha with value for work readiness of 0.921 and employability skills of 0.864. The data analysis technique used path analysis. The result of the study shows that employability skills can be improved through effective implementation of industrial work practice, good training work learning readiness, and vocational competency-based technical skills and non-technical skills.